2011
DOI: 10.1111/j.1365-2125.2010.03834.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication details documented on hospital discharge: cross‐sectional observational study of factors associated with medication non‐reconciliation

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Managing a patient's medication(s) at points around transfer of care is central to patient safety and high quality care.• Medication use at these points carries the potential for miscommunication and medication error.• Processes of reconciliation can help to reduce the prevalence of miscommunication and error, improve continuity of appropriate medication use and improve communication across different settings. However, such processes are resource intensive. WHAT THIS P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 30 publications
8
78
1
2
Order By: Relevance
“…[4][5][6][7][8][9][10] There was no difference in error rates between patients cared for by hospitalists or cardiology attendings and those cared for by house staff, suggesting that clinical experience and expertise are not adequate protections against medication errors at discharge. By contrast, a recent study of an electronic medication reconciliation intervention demonstrated a reduction in provider errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10] There was no difference in error rates between patients cared for by hospitalists or cardiology attendings and those cared for by house staff, suggesting that clinical experience and expertise are not adequate protections against medication errors at discharge. By contrast, a recent study of an electronic medication reconciliation intervention demonstrated a reduction in provider errors.…”
Section: Discussionmentioning
confidence: 99%
“…3 A further set of errors can be made at the time of hospital discharge. [4][5][6][7][8][9][10] Errors include unintentional discontinuation of medication on discharge, [4][5][6][7] inappropriate retention of inpatient medications on discharge, 7,8 and inaccurate changes in dosing or frequency. Medication reconciliation inaccuracies accumulating at all these points of transition create substantial risk for medication errors on hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study involving 1,245 episodes of outpatient care with post-discharge patients, Grimes et al (2011) found that in 50.1% of cases there was at least one prescribing error or lack of documenting or communicating treatment alterations, either in the discharge prescription or discharge summary. Corry et al (2000) found that the information on hospital letters sent to primary care are insufficient to adequately monitor the pharmacotherapy.…”
Section: At the Time Of Dischargementioning
confidence: 99%